Internal Migration as a Social Determinant of Occupational Health and WASH Access in Myanmar - Heidi West; Marlar Than; Thinzar Win; Khin Thein Oo; Kyi Khaing; Thin Thin Aye; San Myint Yi; Su Yi Myo; Su Yi Toe; Maja Milkowska-Shibata; Kristin Melissa; Can Meng; et al. (Ubiquity Press, 2021)
Background: Migration is at an all-time high worldwide, and despite increased focus on international migrants, there is little evidence about internal migrants' exposures to socioeconomic, occupational, and environmental risk factors in low-and middle-income countries. Objective: The aim of this study was to examine differences in occupational health and access to water, sanitation, and hygiene (WASH) between internal migrants and non-migrants. Methods: A face-to-face survey (n = 937) was conducted in Mandalay, Myanmar. Bivariate and multivariate analysis included traditional social determinants such as education, income, occupation, gender, age, and location in addition to internal migration status. Findings: The majority of internal migrants (23% of the total sample) were labor migrants (67.3%), and while common social determinants (e.g., household income, education, and gender) were not statistically different between migrants and non-migrants, these groups reported different occupational profiles (p < 0.001). Migrants had higher odds of being street vendors (AOR = 2.26; 95% CI 1.33-3.85; p = 0.003) and were less likely to work labor jobs such as in factories or construction (AOR = 0.44; 95% CI 0.19-1.00; p = 0.051) when controlling for age, gender, education, and location. Internal migrants had significantly greater probabilities of experiencing some injuries and illness symptoms, such as cuts, vomiting, coughing, heatstroke, and diarrhea at work (p < 0.001). Compared to non-migrants, migrants' households were approximately three times more likely (AOR = 3.45; 95% CI 2.17-5.62; p < 0.001) to have an unimproved source of drinking water and twice as likely (AOR = 1.98; 95% CI 1.10-3.58; p < 0.05) to have unimproved sanitation facilities in their homes. Conclusions: The results underscore the importance of considering internal migration as an aspect of social determinants analyses, and the need for targeting appropriate WASH interventions to address inequities.